MULTIFOCAL ATHEROSCLEROSIS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND ITS COMBINATION WITH METABOLIC SYNDROME - Rzayeva, R.A.; Karimova, N.B.; Abbasova, M.R.; Gurbanov, Y.Z. (World of Medicine and Biology, 2024)
In this article, the results of the frequency of registered cases of multifocal atherosclerosis and plural atherosclerotic plaques in the different vessels of patients with diabetes mellitus type 2 and its combination with metabolic syndrome are presented. It is shown, that in patients with type 2 diabetes mellitus with and without metabolic syndrome, more often both multifocal atherosclerosis and plural atherosclerotic plaques are determined. The incidence of multifocal atherosclerosis was significantly higher in patients with diabetes mellitus (regardless of the presence of concomitant metabolic syndrome) compared to patients without diabetes and metabolic syndrome of similar age and sex composition. Only in patients with diabetes mellitus type 2 and its combination with metabolic syndrome plural atherosclerotic plaques in the same vessels in contrast to patients without diabetes and metabolic syndrome were discovered. Thus, a significant effect of diabetes mellitus on the rapid development and progression of atherosclerosis, which is exacerbated with the accession of the metabolic syndrome, has been demonstrated.